Optical Coherence Tomography - Pier Alberto Testoni (The Scientific World Journal)
Optical coherence tomography (OCT) is an optical imaging modality that performs high-resolution, cross-sectional, subsurface tomographic imaging of the microstructure of tissues. The physical principle of OCT is similar to that of B-mode ultrasound imaging, except that it uses infrared light waves rather than acoustic waves. The in vivo resolution is 10–25 times better (about 10 µm) than with high-frequency ultrasound imaging, but the depth of penetration is limited to 1–3 mm, depending on tissue structure, depth of focus of the probe used, and pressure applied to the tissue surface. In the last decade, OCT technology has evolved from an experimental laboratory tool to a new diagnostic imaging modality with a wide spectrum of clinical applications in medical practice, including the gastrointestinal tract and pancreatico-biliary ductal system. OCT imaging from the gastrointestinal tract can be done in humans by using narrow-diameter, catheter-based probes that can be inserted through the accessory channel of either a conventional front-view endoscope, for investigating the epithelial structure of the gastrointestinal tract, or a side-view endoscope, inside a standard transparent ERCP (endoscopic retrograde cholangiopancreatography) catheter, for investigating the pancreatico-biliary ductal system. The esophagus and esophagogastric junction have been the most widely investigated organs so far; more recently, duodenum, colon, and the pancreatico-biliary ductal system have also been extensively investigated. OCT imaging of the gastrointestinal wall structure is characterized by a multiple-layer architecture that permits an accurate evaluation of the mucosa, lamina propria, muscularis mucosae, and part of the submucosa. The technique may therefore be used to identify preneoplastic conditions of the gastrointestinal tract, such as Barrett's epithelium and dysplasia, and evaluate the depth of penetration of early-stage neoplastic lesions. OCT imaging of the pancreatic and biliary ductal system could improve the diagnostic accuracy for ductal epithelial changes, and the differential diagnosis between neoplastic and non-neoplastic lesions.